The Effects of Extraneous Load on the Relationship Between Self-Regulated Effort and Germane Load Within an E-Learning Environment - Lange, Christopher; Costley, Jamie; Han, Seung-lock (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Online instructors need to avoid unclear and confusing explanations of content, which can reduce the quality of learning. Extraneous load is reflective of poor instruction, in that it directs student effort towards processing information that does not contribute to learning. However, students may be able to manage poor instruction through effort regulation. Students who show high levels of effort have been shown to overcome poor instruction in some cases. This study analyzed survey responses from South Korean university students studying online (n = 1,575) to examine the relationship between self-regulated effort and germane load within varying extraneous load conditions. The experimental design separated extraneous load responses into three conditions (low, medium, high). Within each extraneous load condition, self-regulated effort responses were also separated (low, medium, high). The results showed that as extraneous load increased, self-regulated effort had a weaker relationship with germane load. It was also found that the use of effort regulation is effective only when dealing with low and mid-level extraneous load situations and that use of such strategies within high extraneous load situations was not effective. These results show the importance of imp roving instruction to reduce extraneous cognitive load, in that, not even high levels of effort can overcome poor quality instruction.